A literature review of the current major intraoral digital impression systems and their accuracy - Mezied, Maha; Alnasser, Norah; Owaid, Reema Al; Bakhsh, Rand; Alkhudhayr, Lama; Almazyad, Aseel (International Journal Of Community Medicine And Public Health, 2021)
The accuracy of the intraoral digital impression systems has been previously reported to refer to the quality of the obtained data from the related scanning procedures, irrespective of the quality of the clinical outcomes and the estimated costs. Trueness and precision have been frequently found among studies in the literature as two terms describing the accuracy of the intraoral digital impression systems. Various digital impression modalities have been proposed among studies in the literature and were investigated for estimation of their accuracy. The paper aims to review and discuss the most common literature regarding the current common systems and their accuracy among the different studies in the literature. According to the results, Chairside Economical Restoration of Esthetic Ceramic (CEREC) systems appear to have the highest estimated rates of trueness and precision as compared to the other modalities while the iTero system appears to have the lowest estimated rates. However, some studies have reported contradicting results and the current evidence is mainly based on findings from in vitro investigations. Accordingly, further studies might be needed for further validation of the current evidence and strengthening the quality of the future potential implications for clinicians.